International Association of Geodesy Symposia
DOI: 10.1007/3-540-26932-0_58
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Gravity Variations in GOCE Gradiometric Data

Abstract: Abstract. The accuracy and spatial resolution expected from GOCE gravity gradiometry might deteriorate due to temporal gravity variations, which are mainly induced by mass redistributions in the System Earth. These mass redistributions occur in the atmosphere at various time scales, in the oceans as ocean tides and currents and on the continents as solid Earth tides, loading and hydrological effects. Opposite to GRACE, GOCE is developed to measure the static gravity field. Therefore, any time variable effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…More detailed simulation studies have confirmed that temporal gravity field variations generally remain far below the GOCE noise level (Jarecki et al 2005;Han et al 2006;Moore and King 2010). The extended mission duration now foreseen will hardly change this situation.…”
Section: Goce Versus Gracementioning
confidence: 93%
“…More detailed simulation studies have confirmed that temporal gravity field variations generally remain far below the GOCE noise level (Jarecki et al 2005;Han et al 2006;Moore and King 2010). The extended mission duration now foreseen will hardly change this situation.…”
Section: Goce Versus Gracementioning
confidence: 93%
“…For example Han et al (2004), Jarecki et al (2005) and Han et al (2006) sphere, oceans and hydrology in terms of the geoid and gravity gradients. These studies have shown GOCE to be insensitive to ocean tides and other mass redistributions at the seasonal scale.…”
Section: Introductionmentioning
confidence: 99%